Biodiversity potential and scientific basis for conservation in the Song Hinh - Tay Hoa area, Dak Lak province, Vietnam - Nguyen Dang, Hoi; Le Xuan, Dac; Dang Hung, Cuong; Ngo Trung, Dung; Pham Hong, Phuong; Dinh The, Dung; Pham Mai, Phuong; Luong Van, Dung; Nguyen Cao, Huan; N.A., Poyarkov; A.N., Kuznetsov (Vietnam Journal of Earth Sciences, 2025)
The Song Hinh - Tay Hoa area harbors exceptional ecological and biodiversity values. Two characteristic forest ecosystems are represented: lowland and mid-montane evergreen tropical forests, which collectively support remarkable biodiversity, comprising 1,163 vascular plant species, 58 mammalian species, 219 bird species, 125 reptile and amphibian species, and 65 freshwater fish species. Of these, 41 plant species, 20 mammal species, 32 bird species, 14 reptile species, 6 amphibian species, and 6 freshwater fish species are listed as Near Threatened or higher on the IUCN Red List (2025), the Vietnam Red Data Book (2024), and Government Decree No. 84/2021/ND-CP. A defining feature of the area is its high level of endemism, including several narrowly distributed taxa recorded exclusively within the site. In comparison with the ecological and biological criteria stipulated in the current Law on Biodiversity and the Law on Forestry, the area exceeds the thresholds required, thereby meeting both scientific and practical conditions for designation as a provincial- or national-level nature reserve. Drawing upon these research findings and the integrated analysis of landscape and ecosystem maps, a proposal is made for the establishment of a nature reserve, comprising three functional zones: a strictly protected core (13,708 ha), an ecological restoration zone (23,037 ha), and an administrative and service area (362 ha).  Abramov A.V., Kruskop S.V., Dinh The Dung, V. Dinh Duy, 2022. Mammal survey in Song Hinh Protected Forest, Phu Yen Province, Vietnam. Journal of Tropical Science and Technology, 29, 130–140. Doi: 10.58334/vrtc.jtst.n29.13.Cao Van Cuong, 2018. Research on plant biodiversity conservation management in Pu Luong Nature Reserve, Thanh Hoa Province. PhD thesis in forestry, Hanoi, 173p.Charles M.F., 2019. Field Guide to the Mammals of South-east Asia (2nd Edition). Bloomsbury Wildlife, 416p.Convention on Biological Diversity, Montreal, Quebec, Canada, 1992.Decision 1352/QD-TTg dated November 8, 2024 of the Government of Vietnam on Vietnam's National Biodiversity Conservation Plan for the 2021-2030 period, vision to 2050.Decree 84/2021/ND-CP dated September 22, 2021 of the Government of Vietnam amending and supplementing a number of articles of Decree No. 06/2019/ND-CP dated January 22, 2019 of the Government of Vietnam on management of endangered, precious and rare forest plants and animals and implementation of the Convention on International Trade in Endangered Species of Wild Fauna and Flora. Decree No. 65/2010/ND-CP, dated June 11, 2010 of the Government of Vietnam on detailed regulations and guidance on the implementation of a number of articles of the Law on Biodiversity of Vietnam.Decree No. 91/2024/ND-CP dated July 18, 2024 of the Government of Vietnam on Amending and supplementing a number of articles of Decree No. 156/2018/ND-CP dated November 16, 2018 of the Government detailing the implementation of a number of articles of the Law on Forestry of Vietnam.Duong T.V., Do D.T., Ngo C.D., Nguyen T., 2018. A new species of the genus Leptolalax (Anura: Megophryidae) from southern Vietnam. Zoological Research, 38(3), 181−196. Doi: 10.24272/j.issn.2095-8137.2018.009.Guidelines for Protected Area Management Categories, IUCN, 1994.Huong Manh Kieu, Quy Van Nguyen, Ha Thi Nguyen, Thach Ngoc Do, Hop Van Nguyen, 2022. Plant biodiversity, value, and distribution of Rubiaceae at Hon Ba Nature Reserve, Khanh Hoa province, Vietnam. World Journal of Advanced Research and Reviews, 2022, 14(03), 320–331. Doi: 10.30574/wjarr.2022.14.3.0559.IUCN, Red List of Threatened Species, 2025. http://www.iucnredlist.org.Kon Ka Kinh National Park, 2014. Kon Ka Kinh National Park - an Important Biodiversity Area of the Central Highlands. Agriculture Publishing House, 72p.Kuznetsov Andrey Nikolaevich, 2015. Structure and dynamics of monsoon tropical forests of Vietnam. Dissertation of Doctor of Biological Sciences, Moscow State University named after M.V. Lomonosov, 554p.Le Xuan Dac, 2024. Report on synthesis of published biodiversity research data in the Deo Ca - Hon Vong Phu area, Hanoi, 21p.Linh Manh Nguyen, Shingo Akita, Luong Van Cao, Anh Nguyen Thi Mai, Quang Van Pham, Hung Manh Vu, The Duc Nguyen, Vy Xuan Nguyen, Quan Van Nguyen, Christophe Vieira, 2024. Concise review of the brown algal genus Padina (Dictyotaceae): knowledge in biodiversity, biogeography, potential and scope future research for Vietnam. Vietnam Journal of Marine Science and Technology, 24(4) 399–418. https://doi.org/10.15625/1859-3097/22126.Massimo Sarti, Thung Do Cong, Ngai Nguyen Dang, Thao Dau Van, Trang Cao Thi Thu, Dong Dao Minh, Barbara Calcinai, Carlo Cerrano, 2023. Marine mollusk biodiversity in Northeastern Islands of Vietnam, impact factors and proposing conservation solutions. Vietnam Journal of Marine Science and Technology, 23(4) 331–344. https://doi.org/10.15625/1859-3097/18836.Ngo Dang Nghia, Pham Thi Minh Thu, 2025. Asparagopsis taxiformis: potential and perspective for Vietnam seaweed industry to reduce CH4 emission in animal husbandry. Vietnam Journal of Marine Science and Technology, 25(3) 373–386. https://doi.org/10.15625/1859-3097/21290.Nguyen Dang Hoi (Editor-in-Chief), Ngo Trung Dung, Giang Van Trong, Kuznetsov A.N., 2022. Natural and anthropogenic landscape of Kon Ka Kinh - Kon Chu Rang conservation territiry. Science and Technology Publishing House, Hanoi, 292p.Nguyen Dang Hoi, et al., 2024. Research on the structural and functional organization of tropical forest ecosystems for conservation, restoration and sustainable use: Research results for the period 2020–2022. Report on the results of the project implementation, Hanoi, 121p.Nguyen Dang Hoi, Kuznetsov A.N. (Co-project leader), 2020. Report on ecological survey results in Song Hinh Protection Forest, Phu Yen province, June 2020. Vietnam - Russia Tropical Center, Hanoi, 124p.Nguyen Dang Hoi, Kuznetsov A.N. (Co-project leader), 2021. Report on ecological survey results in Song Hinh Protection Forest, Phu Yen province, June 2021. Vietnam - Russia Tropical Center, Hanoi, 136p.Nguyen Dang Hoi, Kuznetsov A.N., Kuznetsova S.P., 2014. Structural characteristics of forest plant communities in Hon Ba Nature Reserve, Khanh Hoa province. Journal of Tropical Science and Technology, 7, 20–28. Doi: 10.58334/vrtc.jtst.n07.02.Nguyen Dinh Duong, Lai Vinh Cam, 2021. 30-year changes of natural forests under human activities in the Indochina peninsula - case studies in Cambodia, Laos and Vietnam. Vietnam Journal of Earth Sciences, 43(3), 285–300, https://doi.org/10.15625/2615-9783/16196.Nguyen L.T., et al., 2020. The southernmost distribution of the Rhinoceros snake, Gonyosoma boulengeri (Mocquard, 1897) (Reptile, Squamata, Colubridae), in Vietnam. Check List, 16(2), 337−342.Nguyen S.V., Ho C.T., Nguyen T.Q., 2009. Herpetofauna of Vietnam. Edition Chimaira, Frankfurt am Main, 768p.Nguyen Thanh Luan, Nguyen Tai Thang, Hoang Van Ha, Timothy E.M. McCormack,  2021. Field report: Fauna of Tay Hoa and Song Hinh Protection Forests, Phu Yen Province. Asian Turtle Conservation Program-Indo Myanmar Conservation Organization, Hanoi, 29p.Nguyen Thanh Luan, Nguyen Tai Thang, Le Duy, To Van Quang, Nguyen Quoc Dat, Hoang Van Ha, Tran Van Bang, Luu Hong Truong, Timothy E.M. McCormack, 2019. Field report: Flora and fauna of Song Hinh Protection Forest, Song Hinh district, Phu Yen province. Asian Turtle Conservation Program - Indo Myanmar Conservation and Southern Institute of Ecology, Hanoi, 33p.Nguyen Van Long, Thai Minh Quang, Mai Xuan Dat, Nguyen Le Thao My, Hoang Xuan Ben, 2024. Biodiversity of coral reefs and associated seagrass beds in Quy Nhon Bay, Binh Dinh Province. Vietnam Journal of Marine Science and Technology, 24(3) 265–279. https://doi.org/10.15625/1859-3097/19709.Nguyen Viet Luong, Ryutaro  Tateishi,  Akihiko  Kondoh,  Ngo  Duc  Anh,  Nguyen  Thanh    Hoan, Luu The Anh, 2017. Land cover mapping in Yok Don National Park, Central Highlands of Viet Nam using Landsat 8 OLI images. Vietnam Journal of Earth Sciences, 39(4), 393–406. Doi: 10.15625/0866-7187/39/4/10773.Norman Myers, 1991. Four for the Forest's Future. BioScience, 41(7), 511–512. https://doi.org/10.2307/1311796.Paul Jepson, 2013. Biodiversity conservation. University of Oxford. https://www.researchgate.net/publication/259484953.Pham H.H., 1999-2003. An illustrated flora of Vietnam. Ho Chi Minh City: Tre Publishing House, 1–3.Phu Yen province plan for the period 2021-2030, vision to 2050, Hanoi, 2023, 34p.Plan No. 126/KH-UBND dated July 13, 2021 of the People's Committee of Phu Yen province on the implementation of the Vietnam Forestry Development Strategy for the period 2021-2030, vision to 2050 in Phu Yen province.Poyarkov N.A., Nguyen T.V., Popov E.S., Geissler P., Pawangkhanant P., Neang T., Suwannapoom C., Orlov N.L., 2021. Recent progress in taxonomic studies, biogeographic analysis and revised checklist of amphibians in Indochina. Russian Journal of Herpetology, 28(3A), 1–110. https://doi.org/10.30906/1026-2296-2021-28-3A-1-110.Poyarkov N.A., Nguyen T.V., Popov E.S., Geissler P., Pawangkhanant P., Neang T., Suwannapoom C., Ananjeva N.B., Orlov N.L., 2023. Recent progress in taxonomic studies, biogeographic analysis, and revised checklist of reptiles in Indochina. Russian Journal of Herpetology, 30(5), 255–476. https://doi.org/10.30906/1026-2296-2023-30-5-255-476.Takhtajan A., 1997. Diversity and Classification of Flowering Plants. Columbia University Press, New York, 643p.Thai Van Trung, 1999. Tropical forest ecosystems in Vietnam. Science and Technology Publishing House, Hanoi, 298p.Tran Thi Thanh Huong, Nguyen Dang Hoi, Trieu Van Hung, 2018. Characteristics of the tree layer structure of some mixed broadleaf and coniferous forest plant communities in Bidoup - Nui Ba National Park, Lam Dong. Journal of Agriculture and Rural Development, 10, 133–138.Uetz P., Freed P., Aguilar R., Hošek J., 2025. The Reptile Database. The Reptile Database. Online resource available from: http://www.reptile-database.org/ [April 15, 2025].Vietnam Academy of Science & Technology, 2024. Vietnam Red Book. Publishing House for Science and Technology, Hanoi, Vietnam, 1-2, 1250p.Vietnam National Biodiversity Conservation Plan for the 2021-2030 period, vision to 2050, Hanoi, 2024, 37p.Vietnam National Strategy on Biodiversity to 2030, vision to 2050, 2022, Hanoi, 21p.Vu Manh, Nguyen Van Them, 2015. Structure of tree species and the structure of Dipterocarpaceae dominant communities in Cat Tien National Park, Dong Nai province. Journal of Forests and Environment, 73, 9–20.